Juridical Review Of Working Agreements On The Safety Of Ship Crew - Dilfa Nurfadila Lahibu; Mutia Cherawaty Thalib; Julius T. Mandjo (Estudiante Law Journal, 2022)
The purpose of writing is to describe the legal relationship between sea work agreements and work agreements based on the Labor Law in Indonesia and to describe the effectiveness of the implementation of sea work agreements on the work safety of crew members. This type of research uses an approach focused on normative legal research with a legal concept related to analysis and construction carried out with specific methods. In general, in an agreement, there is an object where the parties agree to enter into law to carry out the work. For this reason, the rights and obligations of the crew in the PT AWB work agreement have been implemented. They are guided by statutory regulations, including employers'